Mental health and probation supervision in Ireland - Power, Christina (European journal of probation, 2022)
In 2019, three internal studies were conducted in the Irish Probation Service exploring mental health among persons subject to probation supervision. This paper briefly considers, as context for the studies, the Irish and wider international literature exploring mental health problems among those engaged with probation services and outlines the key findings from the three studies. The studies though limited in scale, scope and methodology were consistent in identifying recurring themes supporting the broader research literature highlighting the prevalence of mental health problems among probation service clients. The paper discusses the key findings and implications for probation policy and practice, and looks to ongoing developments and related new initiatives in the field in Ireland.